Adaptive RISE control for asymptotic rigid-body attitude tracking with additive disturbances. (November 2021) - Wen, Haowei; Yue, Xiaokui; Wang, Zheng; Wang, Xin; Xia, Dongdong
Abstract: This paper presents a novel adaptive RISE (robust integral of the sign of the error) control method for the asymptotic rigid-body attitude tracking with inertia uncertainties and bounded unstructured external C 2 disturbances. By virtue of a specially constructed synthesis of modified dynamic scaling mechanism, integration by parts, and finite escape analysis, the new design provides a simple but intuitive solution to the long-standing open problem in almost all RISE-based control schemes, that is, establishing global asymptotic tracking results without information about exact bounds of the external disturbances and its derivatives. Besides significant improvement on robustness, the proposed adaptation mechanism itself can also be regarded as a new kind of non-CE (non-certainty-equivalent) adaptive formulation, where very few extra dynamic extensions are required to largely recover ideal parameter estimation performance in commonly seen non-CE designs. The structure of the proposed controller is also equivalent to an adaptive feedforward compensator plus a stable low-pass filter whose input contains high gain feedback components, which allows flexible adjustments to establish ideal transient response and avoid chattering. Numerical simulations demonstrate that the above unique features of the proposed method lead to notable advantages over the composite adaptive RISE method. Highlights: Provides a simple solution to the open problem in RISE-based control. Achieves significant order reduction when improving the adaptation performance. Allows flexible adjustments to obtain desired transient behavior. Reduces the conservatism in traditional RISE designs.